2015
DOI: 10.18632/oncotarget.3990
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-specific demethylase (LSD1/KDM1A) and MYCN cooperatively repress tumor suppressor genes in neuroblastoma

Abstract: The chromatin-modifying enzyme lysine-specific demethylase 1, KDM1A/LSD1 is involved in maintaining the undifferentiated, malignant phenotype of neuroblastoma cells and its overexpression correlated with aggressive disease, poor differentiation and infaust outcome. Here, we show that LSD1 physically binds MYCN both in vitro and in vivo and that such an interaction requires the MYCN BoxIII. We found that LSD1 co-localizes with MYCN on promoter regions of CDKN1A/p21 and Clusterin (CLU) suppressor genes and coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 41 publications
(56 reference statements)
2
55
0
Order By: Relevance
“…One recent study showed that c-Myc interacts with histone demethylases KDM4B and KDM4C to regulate mouse embryonic cell stemness (36). The histone demethylase KDM1A has been shown to reprogram the transcriptome of neuroblastoma cells and regulates neuroblastoma xenograft growth (37), cooperating with N-Myc to repress tumor suppressor genes in neuroblastoma (38). We have recently identified that KDM4B physically interacts with N-Myc and maintains the low levels of repressive H3K9me3/me2 marks at Myc target gene loci in neuroblastoma, thereby facilitating N-Myc activity (14).…”
Section: Discussionmentioning
confidence: 99%
“…One recent study showed that c-Myc interacts with histone demethylases KDM4B and KDM4C to regulate mouse embryonic cell stemness (36). The histone demethylase KDM1A has been shown to reprogram the transcriptome of neuroblastoma cells and regulates neuroblastoma xenograft growth (37), cooperating with N-Myc to repress tumor suppressor genes in neuroblastoma (38). We have recently identified that KDM4B physically interacts with N-Myc and maintains the low levels of repressive H3K9me3/me2 marks at Myc target gene loci in neuroblastoma, thereby facilitating N-Myc activity (14).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that MYCN interacts with LSD1 and that the LSD1/MYCN complex controls transcription of tumor suppressor genes such as p21 and CLU [6]. Moreover LSD1 inhibition results in cell growth arrest of cultured NB cells.…”
Section: Resultsmentioning
confidence: 99%
“…Despite concerted worldwide efforts to tackle glioblastoma, patient prognosis remains grim and recurrence is inevitable (Rich, ; Stupp et al ., ). Several histone demethylases, including LSD1, KDM5A, and KDM5B, are upregulated in malignant gliomas, sustaining cell growth, and resistance to chemotherapy (Amente et al ., ; Banelli et al ., ; Black et al ., ; Dai et al ., ; Hayami et al ., ; Tzatsos et al ., ). In the present study, we examined the role of KDM2B in glioblastoma.…”
Section: Discussionmentioning
confidence: 98%